Analisis Pembentukan Moral dalam film Animasi Anak sebagai Tayangan Pendidikan - Masriani, Masriani; Liana, Dina; Syarifudin, Syarifudin (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
This study aimed to analyze and describe the moral values ​​contained in the animated films of Adit and Sopo Jarwo, Nussa and Rara, and the cartoons Upin and Ipin. This research was qualitative descriptive research using samples of the animated Nussa and Rara, and the cartoon Upin Ipin. The data in this study contained religious and moral values. This study described that there were a lot of positive things in the form of habituation of religious and moral values ​​in the form of etiquette before going to bed, eating etiquette, saying bismillah, alms, maintaining cleanliness, doing good deeds, tolerance and helping, not being arrogant, keeping words, praying on time, brotherhood, honesty, love for animals, respect, responsibility, justice, wisdom, self-discipline, caring for others, cooperation, courage, and democracy. Those animated films are highly recommended to be watched by children accompanied by their parents because of its religious and moral values ​​are following the nation's culture and Islam.